GAmBBa: A Platform for Automated Laboratory Workflow Management and Molecular Surveillance Biobanking - Alencar, Andrêza Leite de; Gomes, Saulo; Moura, Karina; Silva, Jessica; Nery Jr, Nivison; Khouri, Ricardo (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
Molecular surveillance and the diagnosis of infectious and neglected diseases require a robust and traceable data flow, spanning from sample collection to the interpretation and reporting of genomic results. However, in many laboratory settings, these processes still depend on manual procedures and spreadsheet-based workflows, which increase the risk of transcription errors, compromise traceability, and limit scalability. At the Molecular Surveillance Platform (PVM) at Fiocruz, these challenges became particularly evident during high-demand scenarios such as the COVID-19 pandemic, when 47,220 samples from 16 municipalities in Bahia, Brazil, were processed to support SARS-CoV-2 diagnosis. In this study, we present GAmBBa (Management of Biological Samples by Barcode), a web-based computational platform designed to automate laboratory workflow management, enable end-to-end sample tracking through barcode identification, integrate communication between laboratory instruments and information systems, and support biobank storage and retrieval. GAmBBa structures the entire sample lifecycle digitally, reducing manual data entry and improving interoperability across laboratory processes. The implementation of GAmBBa has enhanced operational efficiency by minimizing errors, increasing processing capacity, and reducing turnaround time for diagnostic results. The platform proved particularly valuable in high-throughput environments, supporting large-scale molecular surveillance and strengthening the reliability of laboratory outputs. Our findings demonstrate that integrated digital solutions such as GAmBBa are essential to modernize laboratory infrastructures and to support timely and scalable responses to public health demands.